EVALUATION OF FEEDING HYDROPONICS BARLEY ON DIGESTIBILITY AND RUMEN FERMENTATIONS IN AWASSI LAMBS - & et al., Tawfeeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Fifteen Awassi male lambs were randomly distributed to five groups and fed ad libitum roughages: hydroponics barley and/or green alfalfa with different levels, 0: 100, 25: 75, 50: 50, 75: 25 and 100: 0% as roughage experimental diets T1, T2, T3, T4, T5 to study in-vitro and apparent digestibility, rumen fermentations and total rumen bacteria using completely randomized design. Initial weight of replicates were 21.73 kg ± 4.17 kg and 3-4 months old. Concentrate fed at 3% of live body weight based on dry matter basis. Results showed: No differences for in-vitro digestibility, while there were significant increases (p